2020
DOI: 10.4103/ipj.ipj_220_20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychological morbidities and their influential variables among nurses in a designated COVID-19 tertiary care hospital in India: A cross-sectional study

Abstract: Background: Nurses are the main part of the health workforce, performing their duties as frontline warriors against the novel coronavirus pandemic. Nurses involved in the care of infected (COVID-19) patients, may feel more discomfort physically and experience greater psychological morbidities. Aims and Objectives: The main aim of the study is to evaluate the prevalence of anxiety and stress among nurses in a designated COVID-19 hospital and variables that influence thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
3
0
2
Order By: Relevance
“…Having a personal history of any pathology that increased susceptibility to COVID-19 infection was related to higher levels of anxiety and depression, which may be due to a greater concern about infection and its consequences as it implies a higher risk in this group of people. In other areas, similar results have been observed for the presence of depressive symptoms [ 92 ] but not for the anxious type [ 93 , 94 ]. Among HPs from other areas, having a personal history of any mental health disorder, especially those related to substance abuse or depression, was strongly associated with the presentation of a current mental disorder.…”
Section: Discussionsupporting
confidence: 78%
“…Having a personal history of any pathology that increased susceptibility to COVID-19 infection was related to higher levels of anxiety and depression, which may be due to a greater concern about infection and its consequences as it implies a higher risk in this group of people. In other areas, similar results have been observed for the presence of depressive symptoms [ 92 ] but not for the anxious type [ 93 , 94 ]. Among HPs from other areas, having a personal history of any mental health disorder, especially those related to substance abuse or depression, was strongly associated with the presentation of a current mental disorder.…”
Section: Discussionsupporting
confidence: 78%
“…Twenty-two studies (twenty-one quantitative studies and one mixed method study) reported on the prevalence of anxiety among HCWs 13,14,15,16,17,23,24,8,18,29,30,19,25,27,26,31,32,20,21,22,33,34 . Other characteristics of the study findings are presented in Table 2.…”
Section: Anxietymentioning
confidence: 99%
“…Stress was reported in sixteen studies (Fifteen quantitative studies and one mixed method study 13,14,17,18,29,30,19,34,32,21,35,36,27,25,37,26 . Other characteristics of the study findings are presented in Table 2.…”
Section: Stressmentioning
confidence: 99%
“…En el mencionado estudio se consideró como "involucrado con casos confirmados COVID-19" al personal que brindó diagnóstico, tratamiento o cuidados a casos positivos; describiéndose que el 30.75% de este personal padeció de niveles moderados o severos de ansiedad a comparación de un 22.6% en el grupo de personas sin vínculo con casos COVID-19. Asimismo, Garg et al (30) reportó asociación entre el contacto directo con pacientes SARS-CoV-2 + y el desarrollo del trastorno de ansiedad generalizada entre las enfermeras de un hospital en la India, con una muestra de 260 enfermeras. Además, se encontró una fuerte asociación entre la sensación de que "el trabajo me pone en riesgo de contagiarme" y el desarrollo de ansiedad, el 97% de las personas con ansiedad estuvieron de acuerdo en aseverar como cierta esta afirmación.…”
Section: Discussionunclassified
“…Las variables sociodemográficas fueron la edad (categorizada en 3 grupos etarios basados en estudios similares (30,31), el sexo, la ocupación y el tipo de convivencia; por otro lado, las variables confusoras fueron la jornada laboral, la rotación entre áreas de trabajo, el número de guardias nocturnas por semana, el antecedente personal de COVID-19, la presencia de factores predictores de riesgo para COVID-19, el cambio de EPP por semana, la presencia de factores predictores de riesgo para COVID-19 en familiares o la muerte de familiares por COVID-19.…”
Section: Variables Del Estudiounclassified